A novel phase change coolant promoted quality attributes and glutamate accumulation in postharvest shiitake mushrooms involved in energy metabolism. (30th July 2021) - Li, Dong; Wang, Di; Fang, Yida; Li, Li; Lin, Xingyu; Xu, Yanqun; Chen, Hangjun; Zhu, Ming; Luo, Zisheng
Graphical abstract: Highlights: A novel phase change coolant (PCC) was developed for postharvest mushrooms storage. The novel PCC promoted the overall quality attributes of postharvest mushrooms. The novel PCC maintained high energy charge by activating SDH, CCO, and ATPases. Sufficient energy supply promoted glutamate content by inhibiting GDH activity. Abstract: Cold chain transportation is an important link in postharvest logistics of agricultural products. In current study, we developed a novel water-based phase change coolant (PCC), which showed longer effectiveness in maintaining low temperature condition compared with ice, and applied in preserving the postharvest mushrooms. The results showed that the novel PCC effectively inhibited water loss, as well as maintained quality attributes including firmness, color, phenolics, flavonoids, and thus prolonged the shelf-life of mushrooms. Low temperature condition created by the novel PCC treatment maintained high level of energy charge by activating the activities of SDH, CCO, H + -ATPase and Ca 2+ -ATPase, resulting in the delay of postharvest senescence. In addition, sufficient energy supply decreased the consumption of glutamate as carbon skeleton by inhibiting GDH activity, improved glutamate accumulation, and therefore maintained sensory properties as a result. Thus, the novel PCC might be an excellent substitute for ice in cold chain transportation of mushrooms.